A Study on the Sale of Life Insurance Products in Mumbai with Special Reference to Tax Benefits - Mathew, Shobha (SFIMAR Research Review, 2019)
Insurance is a form of risk management primarily used to hedge against the risk of a contingent, uncertain loss. Insurance is defined as equitable transfer of risk of a loss, from one entity to another, in exchange for payment. Customers purchase insurance products for various reasons like availing tax benefits, security, to cover unforeseen risks etc. Also it has been observed that still public insurance companies has better market share. This paper attempts to study factors affecting sale of life insurance products in Mumbai. Excellent past records also affect sale. Hence branding plays a very important role in sale of any products. This paper attempts to study excellent past records, tax benefits and faith in public or private sector insurance companies.